Plenary Speaker. Critical Framing of Transversal Competences: Promoting Intercultural Responsibility through Cross-language and Cross-curricular Teacher Collaborations - Lau, Sunny Man Chu (Cahiers de l’ILOB / OLBI Journal, 2025)
Transversal competences have gained importance in educational programs, particularly with the emphasis on plurilingual approaches in the Common European Framework of Reference. These competences include global citizenship, intercultural communication, and critical thinking. However, many educational statements define these competences narrowly, often reflecting a neoliberal agenda focused on market-oriented education. This paper repositions transversal competences within critical pedagogy and decolonial perspectives, centering language education on students’ critical global perspectives and intercultural reflexivity for civic engagement. Drawing on Guilherme’s concept of intercultural responsibility, I discuss a collaborative action research study with two Quebec elementary teachers (English and French) to show how their cross-language efforts promoted students’ transferable language skills, enhanced students’ cultural awareness, and fostered a reflexive disposition to work across differences and embrace collective responsibility in an increasingly interconnected world.